Penceritaan visual: strategi kreatif iklan komersial bumbu dapur dalam mempertahankan brand image - Hermanto, Agus; Patrianti, Tria; Farisal, Umar; Sanggita, Assya Putri (Program Studi Ilmu Komunikasi UII, 2025)
The purpose of this study is to understand visual stories and creative narratives in advertising through a brand-image approach. The study employs a qualitative approach with narrative analysis. Data collection was conducted through the observation of four TV advertisements for instant cooking spices from various brands, as well as through literature reviews. The results of the study indicate that, in building brand image, instant cooking spices use fragments of life narratives, comparisons, and visual storytelling. In this context, the narrative is constructed through the depiction of values by aligning perception creation with the image, special qualities through associations in image creation via resolution, distinctiveness through identity in image creation through actions, and uniqueness through character and culture in image creation through logical actions.